Genetic studies on continuous flowering in woody plant Osmanthus fragrans - Wang, Qianqian; Gao, Ge; Chen, Xin; Liu, Xiaohan; Dong, Bin; Wang, Yiguang; Zhong, Shiwei; Deng, Jinping; Fang, Qiu; Zhao, Hongbo (Frontiers in Plant Science, 2022)
Continuous flowering is a key horticultural trait in ornamental plants, while the specific molecular regulation mechanism remains largely unknown. In sweet osmanthus (Osmanthus fragrans Lour.), plants based on their flowering characteristics are divided into once-flowering (OF) habit and continuous flowering (CF) habit. Here, we first described the flowering phenology shifts of OF and CF habits in sweet osmanthus through paraffin section and microscope assay. Phenotypic characterization showed that CF plants had constant new shoot growth, floral transition and blooming for one year, which might lead to continuous flowering trait. We performed the transcriptome sequencing of OF and CF sweet osmanthus and analyzed the transcriptional activity of flowering-related genes. Among the genes, three floral integrators, OfFT, OfTFL1 and OfBFT had differential expression during floral transition process in OF and CF habits. The expression patterns of the three genes in one year were revealed. The results suggested that their accumulations were corresponded to the new shoots occurring and floral transition process. Function studies suggested that OfFT acted as a flowering activator, while OfBFT was a flowering inhibitor. Yeast one-hybrid assay indicated that OfSPL8 was a common upstream transcription factor of OfFT and OfBFT, suggesting the vital role of OfSPL8 in continuous flowering regulation. These results provide a novel insight into the molecular mechanism of continuous flowering.